Da’wah of Religious Moderation: The Public Perceptions of Government Policy in West Java - Miharja, Sugandi; Fitriyyah, Ita (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2023)
The study aims to identify the index of religious moderation over public perception of the religious program of moderation as a government policy. This research is a comparative or complementary finding of the facts of the spirit of religious moderation in Indonesia by referring to several research findings from credible research institutions. These findings form the basis for the expression of religious moderation. These research methods include quantitative types. This research method describes the philosophy of the idea of research against a model of research. Samples were taken from Bandung, Cimahi, Garut, and Tasikmalaya, with as many as 878 participants consisting of young people aged 14 and 22 years with students of high school and higher education. The study results showed the index of religious moderation in West Java at 67. The test results supported the hypothesis that government policies in religious moderation influenced the success of religious moderation.